2014
DOI: 10.1098/rsbl.2014.0640
|View full text |Cite
|
Sign up to set email alerts
|

Multiple stressors and multifunctionality: limited effects on an illuminated benthic system

Abstract: The bulk of experiments that study stressor effects on ecosystem functioning consider only individual functions one at a time, and such narrow focus may well bias our understanding of the overall impact on ecosystem functioning. We used data from six published experiments in which marine illuminated sediment systems were exposed to nutrient enrichment, toxicants, sedimentation and warming, either alone or in combination. Measured functions were primary production, community respiration, inorganic nitrogen and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…Thus, metrics of multifunctionality often qualitatively reflected the positive or negative responses of some single functions, while other single functions showed an opposite response or no response (Alsterberg et al, ; Antiqueira et al, ; Bradford et al, ; Ramus et al, ). The inverse was also observed, whereby global change drivers affected some single functions but not others, producing no discernible overall effects on EMF (Alsterberg, Sundback, & Gamfeldt, ; Manning et al, ). In contrast, others found that nearly all single functions responded in the same manner, which was inevitably reproduced in the multifunctionality metric (Chandregowda, Murthy, & Bagchi, ; Luo et al, ; Quero et al, ).…”
Section: Insights From Single and Multiple Functions: Seeing The Forementioning
confidence: 99%
“…Thus, metrics of multifunctionality often qualitatively reflected the positive or negative responses of some single functions, while other single functions showed an opposite response or no response (Alsterberg et al, ; Antiqueira et al, ; Bradford et al, ; Ramus et al, ). The inverse was also observed, whereby global change drivers affected some single functions but not others, producing no discernible overall effects on EMF (Alsterberg, Sundback, & Gamfeldt, ; Manning et al, ). In contrast, others found that nearly all single functions responded in the same manner, which was inevitably reproduced in the multifunctionality metric (Chandregowda, Murthy, & Bagchi, ; Luo et al, ; Quero et al, ).…”
Section: Insights From Single and Multiple Functions: Seeing The Forementioning
confidence: 99%
“…The effects of the 2 SOPCs (potential toxicants and nutrients) in this scenario could be largely offsetting (toxicity effects on the aquatic ecosystem versus enhancement from added nutrients [Prosnier et al ]), could be dominated by either toxicity or enhancement, or could be more complex and less direct. For example, in a shallow‐water sediment system, Alsterberg et al () found that toxicity to grazers decreased predation (a top–down process), resulting in an increase in algal biomass that mimicked the effects of nutrient enrichment (a bottom–up process). Lozano and Pratt () demonstrated that community nutrient status affected both the magnitude of effect and the rate of recovery following stress, with increased nutrient status increasing resistance to the effects of the herbicide diquat to the periphyton community.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, some species or functional traits may be tolerant to some contaminants, but not to others. Furthermore, different stressors or toxic contaminants can have positive, negative or interactive effects on individual functions (Alsterberg, Sundbäck, & Gamfeldt, 2014). Finally, the magnitude of impacts is posited to be directly and positively linked to the concentration of the contaminant and period of exposure, but experimental results within and among studies are mixed (e.g.…”
Section: Introductionmentioning
confidence: 99%